Dependencies between Variables from the Area of the Monetary and Fiscal Policy in the European Union Countries - Stawska, Joanna (Comparative Economic Research. Central and Eastern Europe, 2021)
Research background: The core of coordinating a monetary and fiscal policy (policy mix) is based on combining both policies to achieve goals related to price stability, as well as economic growth and employment. In turn, the decisions of economic authorities in the monetary-fiscal game have a significant impact on economic variables in the economy. In the economic literature, the importance of monetary and fiscal policy coordination is emphasized as it has a positive effect on the stability of the economy. Purpose of the article: The aim of the article is to identify the dependencies between variables in the scope of fiscal policy and monetary policy under existing economic conditions and then assess their impact on the economy in the EU countries. Methods: To achieve this objective, the following research methods were used: a review of the scientific literature, a presentation of statistical data, and statistical research methods. Findings & Value added: The rationale for adopting such issues is to examine the impact of the financial crisis on the decisions of central banks and governments in the EU. The financial crisis has affected a change in the approach to conducting monetary and fiscal policy. The changing economic conditions forced economic authorities to take many decisions that affected the interaction between the central bank and the governments in the EU Member States. In many EU countries in the discussed period, there were significant interdependencies between variables in both monetary and fiscal policy.